HARMONI SOSIAL BERBASIS BUDAYA GUGUR GUNUNG - Imas Setiyawan (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
Culture is one form of community group behaviors in a region. The Javanese society is rich with traditions that have been passed down for generations since the days of the ancients. Gugur Gunung is one of the traditions carried out in Jembul community for generations. It is interesting to find out more in detail the tradition of this tradition, which also plays a role in strengthening relations between individuals in the village. This study uses a qualitative approach, through interview techniques, observation and documentation in conducting the data to find answers to the research problem. The results of research found several facts: first, Gunung Gugur became the field of social harmony in the village of Jembul; this tradition brings the social life in the community to be more harmonious. Second, the community considers the need for cooperation in social life to solve social problems, including issues of welfare that have not been evenly distributed, for which Gugur Gunung provides a solution; and the third is that this tradition involves all elements of the village community in Jembul that have been carried down from generation to generation .Keywords: Gugur Gunung, Harmony, Jembul Village